Surface Structure and Phase Composition of TiO2 P25 Particles After Thermal Treatments and HF Etching - Uddin, M. Jasim; Cesano, Federico; Chowdhury, Aminur Rashid; Trad, Tarek; Cravanzola, Sara; Martra, Gianmario; Mino, Lorenzo; Zecchina, Adriano; Scarano, Domenica (Frontiers in Materials, 2020)
The anatase to rutile phase transformation via thermal and chemical (HF etching) routes of TiO2 P25 have been investigated. The treatment parameters and properties of the resulting anatase and rutile nanoparticles are analyzed and discussed. Since the nature of TiO2 surfaces plays a significant role in determining the physical and chemical properties of the TiO2 nanoparticles, it is important to investigate the surface structure including the morphology, the main exposed faces, the defectiveness, to be correlated with their peculiar properties and then reactivity. Herein, we report an infrared spectroscopy investigation, by means of the adsorption of CO probe molecule at low temperature, including 12CO and 12CO-13CO isotopic mixtures, at the surface sites of TiO2 P25, previously heated from room temperature to 1023 K under vacuum conditions. The same FTIR experiments were adopted on HF-etched TiO2. X-ray diffraction and transmission electron microscopy analyses were adopted to elucidate the role played by the thermal and the HF-etching treatments in modifying not only the distribution of exposed surfaces but even the phase composition of the pristine TiO2 P25 samples, which are initially dominated by the most thermodynamically stable (101) facets of the anatase phase. The present study helps in the crystal and exposed facet engineering for the development of highly efficient photocatalysts.